Lingual Raynaud's phenomenon in a patient with mixed connective tissue disease. Issue 2 (14th December 2021) - Gilbert, Emily L.
Key points: Raynaud's phenomenon may occur as a primary problem or secondary to an autoimmune disease such as scleroderma, mixed connective tissue disease, SLE, or Sjogren's. Lingual Raynaud's is rare, but it is important to recognize as it is often attributed to autoimmune disease. There is a wide range of symptoms in lingual Raynaud's from asymptomatic to severe, throbbing pain. Meticulous history taking is essential. Abstract : Lingual Raynaud's phenomenon in a selfie photograph in a woman with mixed connective tissue disease